Creation of Cattle Ranches, grazing route and reserves as solutions to Herders-Farmers Conflict in Northern Nigeria - Giwa, Muhammad Abubakar; Nur Hafizah Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2024)
In order to address the violent disputes between herders and farmers in Northern Nigeria, this article looked at the establishment of ranches, cattle routes, and grazing reserves. It also looked at how conflict is a social reality that exists in all human social systems, whether they are in cities or rural areas. It observes that disagreements are a common cause of conflict, particularly between the two opposing factions, the "herders," who are primarily Fulani and Muslim migrants seeking better pasture for their livestock, and the crop farmers, who are primarily from agrarian backgrounds. For data gathering, the paper used secondary sources such books, journals, articles, newspapers and other internet sources. The study discovered that there are a number of reasons why farmers and herdsmen in Northern Nigeria clash. Climate change badly executed government policies, illiteracy, a lack of a solid Alternative Dispute Resolution Mechanism (ADRM), anger and hostility brought on by the loss of life and property, and so forth are a few of these. The report suggested that pasture areas, livestock routes, and ranches be established in order to settle the disputes. The report also suggested that in order to stop the threat, the Federal Government of Nigeria should set up a practical ADRM and make sure that policies are implemented effectively. Additionally, it recommended a broad education campaign to inform the opposing sides of the risks their ceaseless fighting poses to Nigeria's progress as a developing nation.